OP73 Systematic review of dietary trans-fat reduction policies: evidence for an effectiveness hierarchy?. (13th September 2016) - Hyseni, L; Bromley, H; Lloyd-Williams, F; O'Flaherty, M; Kypridemos, C; Guzman, M; Pearson-Stuttard, J; Capewell, S
Abstract : Background: The four major risk factors now prioritised in WHO non-communicable disease prevention strategies are tobacco, alcohol, physical inactivity and, crucially poor diet. However, trans-fatty acid intake in most countries still exceeds the WHO target of 2 g/day, mainly reflecting consumption of industrial trans-fats in junk food. Furthermore, the most effective policies for reducing transfats remain unclear. We therefore systematically reviewed the evidence on trans-fat policy interventions to inform future preventions strategies. In addition, we compared "upstream" interventions targeting populations with "downstream" interventions targeting individuals. Methods: A pre-piloted search strategy was used to systematically search six electronic databases (Cinahl, CRD, CDSR, ovidMedline, SCI and SCOPUS) for papers evaluating the effectiveness of trans-fat interventions, with gram/day as the main outcome measure. Two researchers independently screened, extracted and graded the papers for quality. Each study was categorised on a continuum ranging from "downstream" interventions targeting individuals (dietary counselling in individuals, worksites and communities; media campaigns or nutrition labelling) to more "upstream" interventions targeting the entire population (voluntary and mandatory reformulation, regulatory and fiscal interventions). Comprehensive strategies involving multiple interventions were also considered. This systematic review used a narrative synthesis to summarise and compare the effectiveness of different interventions. Results: After screening 976 candidate papers, a total of 21 papers were included in this systematic review: 13 empirical studies and eight modelling studies. Quality was variable. The largest reductions in trans-fat intake were seen in Denmark. Multiple interventions achieved a reduction from 4.5 g/day in 1976 to 1.5 g/day in 1995 and then virtual elimination after a legislative ban in 2005. The USA is now seeking to emulate this success. No studies quantifying tax interventions were identified. Reformulation of food products reduced trans-fat content by an average of −2.7 g/day. Worksite interventions achieved reductions averaging −1.2 g/day, followed by food labelling, approximately −0.7 g/day. Dietary counselling targeting individuals achieved the lowest reductions in trans-fat intake (−0.2 g/day). Conclusion: Legislative bans to eliminate trans-fats from food products appear the most effective strategy to reduce trans-fat intake, as achieved in Denmark (and the USA). However this approach remains underused. Reformulation and other multi-component interventions can also achieve useful reductions. By contrast, more "downstream" interventions targeting individuals consistently achieve much smaller reductions. Future prevention strategies might therefore wish to consider this 'effectiveness hierarchy' in order to achieve the largest reductions in trans-fats intake. Implications for controlling other harmful nutrients such as salt or sugar might also be considered.